THE MEANING OF THE VERB “TO SOUND” IN MUNA LANGUAGE: NATURAL SEMANTIC METALANGUAGE - La Aso (RETORIKA: Jurnal Ilmu Bahasa, 2017)
Abstract This paper aims at investigating the variations of lexicon having meaning of “produce of sound” in Muna language based on natural semantics metalanguage. The data collecting was done by participant speaking and scrutinize methods through interview and noting techniques. It was analyzed by using natural semantics metalanguage (NSM), an approach to investigate various lexicons with principle “one form for one meaning and one meaning for one form”. Based on the result of this study founded that meaning of “produce of sound” of Muna can be expressed by a number of lexicons and each form has distinctive meaning like in the lexicons of kobheghu, kobhondu, kotighi, kopisi, korasa, korangku, kondii, konduu, kopere, kombote, kopaka, koradha, kobuu, korapa, and kohuhu. All lexicons of Muna language has meaning ‘produce of sound’. The use of each lexicon depends on the sounded object/tool, object/tool that create the sound, and the way of creating the sound. Keywords: produce of sound, natural semantics metalanguage, distinctive